Vesicular Trafficking and Signaling for Cytokine and Chemokine Secretion in Mast Cells - Blank, Ulrich; Madera-Salcedo, Iris Karina; Danelli, Luca; Claver, Julien; Tiwari, Neeraj; Sánchez-Miranda, Elizabeth; Vázquez-Victorio, Genaro; Ramírez-Valadez, Karla Alina; Macias-Silva, Marina; González-Espinosa, Claudia (Frontiers in Immunology, 2014)
Upon activation mast cells (MC) secrete numerous inflammatory compounds stored in their cytoplasmic secretory granules (SG) by a process called anaphylactic degranulation, which is responsible for type I hypersensitivity responses. Prestored mediators include histamine and mast cell proteases but also some cytokines and growth factors making them available within minutes for a maximal biological effect. Degranulation is followed by the de novo synthesis of lipid mediators such as prostaglandins and leukotrienes as well as a vast array of cytokines, chemokines and growth factors, which are responsible for late phase inflammatory responses. While lipid mediators diffuse freely out of the cell through lipid bilayers, both anaphylactic degranulation and secretion of cytokines, chemokines and growth factors depends on highly regulated vesicular trafficking steps that occur along the secretory pathway starting with the translocation of proteins to the ER. Vesicular trafficking in mast cells also intersects with endocytic routes, notably to form specialized cytoplasmic granules called secretory lysosomes. Some of the mediators like histamine reach granules via specific vesicular monoamine transporters directly from the cytoplasm. In this review, we try to summarize the available data on granule biogenesis and signaling events that coordinate the complex steps that lead to the release of the inflammatory mediators from the various vesicular carriers in mast cells.